THE STUDY OF MATERNAL AND PERINATAL OUTCOME IN ANTEPARTUM HEMORRHAGE - Dr. Sushma Rachel S, Dr. Nagarathna Gopala (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Objective: To study the incidence, demographic profile, maternal and perinatal outcome in cases ofAntepartum Hemorrhage (APH).